Educational Video Using the 3D Hologram Technique in Kindergarten Learning Methods - Ariska Putri; Indri Raina (Universitas Amikom Purwokerto, 2023)
Based on research observations when carrying out observation and interview activities at the DiponegoroWangon Kindergarten with informants, based on the curriculum the reason for taking traditional transportation equipment material is because this material requires teaching aids that display real visuals besides that examples of traditional transportation equipment toys are increasingly rare it's even rare to get, because toy companies no longer produce traditional means of transportation anymore but instead produce new, more sophisticated toys. To avoid this, teachers can develop learning strategies by utilizing various media and learning resources. The design of 3D hologram visualization media for traditional and modern transportation material is considered appropriate, because with this media students have learning resources that can be used for independent study and display animation that is quite interesting to support the learning process. The system development method used is MDLC. This research begins with sequential stages such as pre-production, production and post-production. The results are in the form of 3D animation designing a visualization media for the introduction of traditional transportation using 3D holographic techniques in the form of mp4.